2022
DOI: 10.1186/s12876-022-02368-w
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic features of oxyntic gland adenoma and gastric adenocarcinoma of the fundic gland type differ between patients with and without Helicobacter pylori infection: a retrospective observational study

Abstract: Background The endoscopic features of oxyntic gland adenoma and gastric adenocarcinoma of the fundic gland type have not been fully investigated in relation to Helicobacter pylori infection status. We compared the morphology, color, and location of these lesions between patients with and without H. pylori infection. Methods We retrospectively enrolled 165 patients (180 lesions) from 10 institutions. We divided the patients into the (i) Hp group (pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Recently, the incidence of early gastric cancer has increased significantly with the application of narrow-band imaging (NBI) magnifying endoscopy [10]. Many H. Pylorinegative gastric adenocarcinomas, including GEN-FGML, have been reported [2,6,[10][11][12][13][14][15][16][17]. In 2021, GEN-FGML was classified into OGA, GA-FG, and GA-FGM, based on cell differentiation and histological features [4].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the incidence of early gastric cancer has increased significantly with the application of narrow-band imaging (NBI) magnifying endoscopy [10]. Many H. Pylorinegative gastric adenocarcinomas, including GEN-FGML, have been reported [2,6,[10][11][12][13][14][15][16][17]. In 2021, GEN-FGML was classified into OGA, GA-FG, and GA-FGM, based on cell differentiation and histological features [4].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study on 165 patients investigated whether there are distinct endoscopic findings in patients with a current or prior history of H. pylori infection in comparison to those without the infection. The study revealed that H. pylori infection was significantly associated with tumors that were flat or in atypical locations of the stomach [ 11 ]. However, in our study, the patient presented with a typical lesion despite his prior H. pylori infection status.…”
Section: Discussionmentioning
confidence: 99%
“…This study is a subgroup analysis of our recently published article reporting the clinicopathologic features of 165 patients with 180 oxyntic gland adenomas and GA-FG lesions ( 15 ). We excluded 24 patients for whom H .…”
Section: Methodsmentioning
confidence: 99%
“…Histological diagnoses were based on endoscopic biopsy, endoscopic mucosal resection, endoscopic submucosal dissection, or surgical resection ( 14 , 15 ). We compared the patient’s sex, age at diagnosis, H .…”
Section: Methodsmentioning
confidence: 99%